2021
DOI: 10.3390/foods10050922
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of In-Store Interventions to Impact Customers to Purchase Healthier Food and Beverage Products in Real-Life Grocery Stores: A Systematic Review and Meta-Analysis

Abstract: Grocery stores are important settings to promote healthier food and beverage choices. The present paper aims at reviewing the effectiveness of different types of in-store interventions and how they impact sales of different product category in real grocery stores. Systematic search was conducted in six databases. In-store interventions were categorized according to the framework by Kraak et al. (2017) into one or more of eight interventions (e.g., place, profile, portion, pricing, promotion, healthy default pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 85 publications
0
26
0
Order By: Relevance
“…Upcharges for the allowable default beverages are clearly contrary to the intent of SB1192 because the upcharges likely discourage those selections among price-conscious consumers. Prior evidence shows that pricing impacts beverage choice (30) , with studies conducted in stores demonstrating that cost, in combination with promotion and prompting, effectively impacts purchasing behaviour (31) . Price is an especially important factor for low-income consumers, who are significantly more conscious of cost and value than higher income consumers (38) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Upcharges for the allowable default beverages are clearly contrary to the intent of SB1192 because the upcharges likely discourage those selections among price-conscious consumers. Prior evidence shows that pricing impacts beverage choice (30) , with studies conducted in stores demonstrating that cost, in combination with promotion and prompting, effectively impacts purchasing behaviour (31) . Price is an especially important factor for low-income consumers, who are significantly more conscious of cost and value than higher income consumers (38) .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found increased ordering of more healthful items (17,29) and reduced energetic intake (29) following the implementation of healthy default menus. Additional research indicates that cost also impacts beverage choice (30) , with in-store studies demonstrating that pricing, in combination with promotion and prompting, effectively impacts purchasing behaviour (31) . However, evidence regarding the impact of healthy default policies on pricing is mixed, with some studies finding price increases (29) and others reporting no change in prices (32,33) .…”
mentioning
confidence: 99%
“…Relatively little research has examined the impact of removing less healthy foods from checkout areas on purchasing behaviour. Two recent systematic reviews reported that the majority of nudge interventions focused on in‐store promotions (for healthier foods), information provision, increased availability of healthier foods and, to a lesser extent, pricing (Adam & Jensen, 2016; Slapø et al, 2021). Nonetheless, the findings from these reviews are supportive of in‐store interventions being beneficial for diet‐related behaviours, although some caution is needed because of the lack of high‐quality studies.…”
Section: Introductionmentioning
confidence: 99%
“…Although adherence was somewhat sustained at 6 months, the results were not statistically significant at this timepoint. Previous research has shown similar short-term success in increasing fruits and vegetable consumption, but not long-term success 5 , and a meta-analysis of store-based diet interventions also showed mixed results 6 . However, the lack of sustained, long-term success up to now should not discourage us from delivering interventions at food retailers.…”
mentioning
confidence: 97%